Environmentally stable lead-free cesium bismuth iodide (Cs3Bi2I9) perovskite: Synthesis to solar cell application. (November 2020) - Waykar, Ravindra; Bhorde, Ajinkya; Nair, Shruthi; Pandharkar, Subhash; Gabhale, Bharat; Aher, Rahul; Rondiya, Sachin; Waghmare, Ashish; Doiphode, Vidya; Punde, Ashvini; Vairale, Priti; Prasad, Mohit; et al.
Abstract: In this paper, we synthesized lead-free cesium bismuth iodide (Cs3 Bi2 I9 ) perovskite films by solution process using one-step spin-coating technique. Formation of Cs3 Bi2 I9 perovskite was confirmed by X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy and transmission electron microscopy analysis. The XRD analysis showed that all Cs3 Bi2 I9 perovskite films were polycrystalline in nature, with hexagonal crystal structure and preferred-orientation along (006) direction. The environmental stability of Cs3 Bi2 I9 perovskite was confirmed by XRD analysis and UV–visible spectroscopy. Multiple XRD and UV–Vis spectra taken after long time spans revealed the stable nature of Cs3 Bi2 I9 perovskite films. The UV–visible spectroscopy and photoluminescence analysis showed that the perovskite films absorbed strongly in the visible region and had an optical band gap of ~2.1 eV. Surface morphology of Cs3 Bi2 I9 perovskite over the entire substrate surface was investigated using scanning electron microscopy. Thermo-gravimetric analysis showed that Cs3 Bi2 I9 perovskite was thermally stable up to ∼ 420 °C. Finally, solar cells fabricated using Cs3 Bi2 I9 perovskite material showed maximum power conversion efficiency (PCE) of 0.17%, with short circuit current density of 1.43 mA/cm 2, open circuit voltage of 0.37 V and fill factor of 32%. Applying compositional engineering and optimizing the device structure should further improve the PCE. These results are a significant step toward fabrication of Cs3 Bi2 I9 perovskite-based solar cells. Highlights: Synthesis of lead-free Cs3 Bi2 I9 perovskite films by spin coating. Films have hexagonal crystal structure with (006) preferred orientation. Cs3 Bi2 I9 perovskite is thermally stable up to ~420 °C. Maximum power conversion efficiency is 0.17%. A significant step toward fabricating Cs3 Bi2 I9 perovskite based solar cells.